Centrifugation-Mediated Crystal Growth of Attractive Colloids for Band Edge Lasing - Jung, Yongseok; Park, Sanghyuk; Lee, Sang Seok; Kim, Shin-Hyun (Wiley - V C H Verlag GmbbH & Co., 2024)
Attractive depletion interactions are utilized to organize colloidal particles into crystalline arrays with high crystallinity through spontaneous phase separation. However, uncontrolled nucleation frequently leads to the formation of crystalline grains with varied crystal orientations, which hampers the optical performance of photonic crystals. Here, colloidal crystals have been engineered with uniform orientation and high surface coverage by applying centrifugal force during the depletion-induced assembly of polystyrene particles. The centrifugal force encourages the particles to move toward the bottom surface, which fosters heterogeneous nucleation and supports rapid crystal growth, yielding densely-packed and uniformly-arranged crystal grains with high reflectivity. This study has observed that the nucleation and crystal growth behavior is significantly influenced by the salt concentration. Based on the pair potentials, the transition boundary has been quantitatively analyzed between fluid and crystal phases and identified the threshold for homogeneous nucleation. Utilizing the high-reflectivity colloidal crystals, band-edge lasing is achieved by dissolving the water-soluble dye into the aqueous suspensions. Upon optical excitation, a lasing emission characterized is observed by a narrow spectral width at the short-wavelength band edge. Notably, the laser wavelength can be adjusted by altering the salt concentration or particle diameter, offering a versatile approach to tuning the optical properties. Colloidal photonic crystals with uniform orientation and high surface coverage are produced by applying centrifugal force during the depletion-induced assembly of polystyrene particles. This force encourages the particles to move toward the bottom surface, facilitating heterogeneous nucleation and rapid unidirectional crystal. These high-quality colloidal crystals enable band-edge lasing with a narrow spectral emission. image